Epidemiological survey of antinuclear antibodies in healthy population and analysis of clinical characteristics of positive population - Li, Xiaoyan (J Clin Lab Anal, 2019)
BACKGROUND: In China, the incidence of autoimmune diseases is gradually increasing. To decrease the misdiagnosis rate of autoimmune diseases, we conducted an epidemiological investigation about the presence of antinuclear antibody (ANA) in healthy populations and analyzed the clinical characteristics of healthy population with both high titer of ANA and positive anti‐SSA and AMA‐M2. METHODS: Serum ANA titers were detected by indirect immunofluorescence (IIF), and other 15 types of ANA‐specific antibodies were detected by line immunoassays. RESULTS: In 25 110 individuals for routine examination, the positive rate of ANA titer >1:100 was 14.01%, of which the positive rate of female (19.05%) was higher than that of male (9.04%; P < 0.01). The positive rate of ANA titer >1:320 was 5.93%, of which the positive rate of female (8.68%) was higher than that of male (3.21%; P < 0.01). The specific antibodies were detected in 1489 of ANA‐positive people with titer >1:320, and the top three detected antibodies were anti‐Ro‐52 (212), AMA‐M2 (189), and anti‐SSA (144). The abnormal rate of blood routine test, liver function test, and other clinical indicators in AMA‐M2–positive population was significantly different from those in the control group. The abnormal rate of blood routine test, liver function test, and immune index in anti‐SSA–positive population was higher than those in control group. CONCLUSION: There was a high prevalence of ANA positive in healthy population. To avoid misdiagnosis, those who had symptoms of abdominal discomfort, pruritus, or fatigue with abnormal results of blood routine and liver function test should be examined for ANA, AMA‐M2, anti‐SSA as early as possible.